The role of IL-1 in adipose browning and muscle wasting in CKD-associated cachexia - Wai W. Cheung (Nature Portfolio, 2021)
Abstract Cytokines such as IL-6, TNF-α and IL-1β trigger inflammatory cascades which may play a role in the pathogenesis of chronic kidney disease (CKD)-associated cachexia. CKD was induced by 5/6 nephrectomy in mice. We studied energy homeostasis in Il1β −/− /CKD, Il6 −/− /CKD and Tnfα −/− /CKD mice and compared with wild type (WT)/CKD controls. Parameters of cachexia phenotype were completely normalized in Il1β −/− /CKD mice but were only partially rescued in Il6 −/− /CKD and Tnfα −/− /CKD mice. We tested the effects of anakinra, an IL-1 receptor antagonist, on CKD-associated cachexia. WT/CKD mice were treated with anakinra (2.5 mg/kg/day, IP) or saline for 6 weeks and compared with WT/Sham controls. Anakinra normalized food intake and weight gain, fat and lean mass content, metabolic rate and muscle function, and also attenuated molecular perturbations of energy homeostasis in adipose tissue and muscle in WT/CKD mice. Anakinra decreased serum and muscle expression of IL-6, TNF-α and IL-1β in WT/CKD mice. Anakinra attenuated browning of white adipose tissue in WT/CKD mice. Moreover, anakinra normalized gastrocnemius weight and fiber size as well as attenuated muscle fat infiltration in WT/CKD mice. This was accompanied by correcting the increased muscle wasting signaling pathways while promoting the decreased myogenesis process in gastrocnemius of WT/CKD mice. We performed qPCR analysis for the top 20 differentially expressed muscle genes previously identified via RNAseq analysis in WT/CKD mice versus controls. Importantly, 17 differentially expressed muscle genes were attenuated in anakinra treated WT/CKD mice. In conclusion, IL-1 receptor antagonism may represent a novel targeted treatment for adipose tissue browning and muscle wasting in CKD.